A testbed for evaluation of innovative turbo MIMO-OFDM architectures - Horseman, T; Webber, J; Abdul-Aziz, M.K; Piechocki, R; Nix, A; Beach, M; Fletcher, P (5th European Personal Mobile Communications Conference 2003, 2003)
WLANs operating in the 5 GHz band have been standardized by the IEEE (North America), ETSI (Europe) and ARIB (Japan), and a harmonized physical layer is specified offering up to 54 Mbits/s using rate adaptive coded orthogonal frequency division multiplexing (COFDM). Multiple input multiple output (MIMO) antenna architectures coupled with soft input soft output (SISO) iterative decoding algorithms represent a revolutionary approach to the design of WLANs. At present, these techniques are the subject of intense theoretic research. In this paper, the performance of a newly proposed iterative MIMO-OFDM architecture is explored using MIMO channel data captured in the 5 GHz band. Theoretically, this technology has the potential to significantly increase future WLAN data rates. However, little practical evaluation has been reported in the literature. To address this situation, this paper also describes the construction of a broadband 5 GHz MIMO-OFDM testbed. This advanced baseband/RF platform will be used in the future to evaluate innovative MIMO-OFDM WLAN architectures.